On nearly S-paracompactness (2021)
- The objective of the present work is to introduce the notion of α-nearly S-paracompact subset, which is closely related to α-nearly paracompact and αS-paracompact subsets. Moreover, we study the invariance under direct and inverse images of open, perfect and regular perfect functions of the nearly S-paracompact spaces [10] and analyze the behavior of such spaces through the sum and topological product.